PENGARUH KETEPATAN WAKTU DAN KEMUDAHAN PENGGUNAAN APLIKASI ACCESS BY KAI TERHADAP KEPUASAN PENUMPANG KAI DI STASIUN RANCAEKEK - Dina Sonia; Dea Restika (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of punctuality and ease of use of the Access by KAI application on passenger satisfaction of KAI Commuterline Bandung Raya Daop 2 at Rancaekek Station. Issues related to train delays and technical problems in using the Access by KAI application are suspected to affect passenger satisfaction. This research employs a quantitative approach using a survey method by distributing questionnaires to passengers who use the Access by KAI application. The independent variables in this study are punctuality and ease of use of the application, while the dependent variable is passenger satisfaction. Data analysis was conducted using validity tests, reliability tests, multiple linear regression analysis, and hypothesis testing. The results indicate that punctuality and ease of use of the Access by KAI application have a significant effect on passenger satisfaction, both simultaneously and partially.